2020
DOI: 10.21037/tcr-20-3149
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensively analyze the expression and prognostic role for ten-eleven translocations (TETs) in acute myeloid leukemia

Abstract: Background: The ten-eleven translocation (TET) family oxidize 5-methylcytosines (5mCs) and promote the locus-specific reversal of DNA. The role of TETs in acute myeloid leukemia (AML) is mostly unknown. Methods: TETs mRNA expression levels were analyzed via Gene Expression Profiling InteractiveAnalysis (GEPIA). The association TETs expression levels and methylation with prognosis by UALCAN GenomicScape, and METHsurv. We analyzed TETs' aberration types, located mutations, and structures via cBioPortal. GeneMANI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…23 Using a gene set cancer analysis (GSCALite), both TET1 and TET2 genes were shown to be sensitive to belinostat. 26,27 Mutations in TET2 and RHOA were also present in our patient case, and the use of belinostat may have eventually led to a very good partial response of the disease, allowing an allo-SCT to be performed. A sub-analysis of the BELIEF study presented data from patients who underwent a hematopoietic SCT (HSCT) after belinostat treatment: a total of 12 patients, including two patients with nTFHL-AI, received either an ASCT (four patients) or an allo-SCT (eight patients).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…23 Using a gene set cancer analysis (GSCALite), both TET1 and TET2 genes were shown to be sensitive to belinostat. 26,27 Mutations in TET2 and RHOA were also present in our patient case, and the use of belinostat may have eventually led to a very good partial response of the disease, allowing an allo-SCT to be performed. A sub-analysis of the BELIEF study presented data from patients who underwent a hematopoietic SCT (HSCT) after belinostat treatment: a total of 12 patients, including two patients with nTFHL-AI, received either an ASCT (four patients) or an allo-SCT (eight patients).…”
Section: Discussionmentioning
confidence: 60%
“…It is suggested that HDAC inhibitors may help maintain an acetylated and active TET2 and therefore prevent the abnormal DNA methylation that occurs in cancer 23 . Using a gene set cancer analysis (GSCALite), both TET1 and TET2 genes were shown to be sensitive to belinostat 26,27 . Mutations in TET2 and RHOA were also present in our patient case, and the use of belinostat may have eventually led to a very good partial response of the disease, allowing an allo‐SCT to be performed.…”
Section: Discussionmentioning
confidence: 70%
“…It is suggested that HDAC inhibitors may help maintain an acetylated and active TET2 and therefore prevent the abnormal DNA methylation that occurs in cancer 21 . Using a gene set cancer analysis (GSCALite), both TET1 andTET2 genes were shown to be sensitive to belinostat 23,24 . Mutations in TET2 andRHOA were also present in our patient case, and the use of belinostat may have eventually led to a very good partial response of the disease, allowing an allo-SCT to be performed.…”
Section: Discussionmentioning
confidence: 99%